Replication Seminar on Sustainable Development - Saharudin, Ramli (2021)
KUANTAN, 27 July 2021 - MYSUN-UMP, one of the partners under an international grant co-funded by Erasmus+ Programme of European Union via a project known as Malaysia Sustainable University Campus Network (MYSUN), successfully organised a replication seminar based on training for trainers (TOT) of MYSUN project.